2015
DOI: 10.4103/2394-4722.157068
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of extracellular microRNAs in medulloblastoma

Abstract: Aim: Medu lloblastoma (MB) is the most common malignant brain tumor in children. The crucial role of extracellular-microRNAs (ex-miRNAs) in cancer has been widely recognized; however, their role in MB remains unknown. This study aimed to investigate MB-driven ex-miRNAs. Methods: Microarray analysis was used to disclose the identity and quantity of key miRNAs excreted in culture-medium (CM) of 3 human MB cell lines and cere brospinal fl uid (CSF) of brain tumors (including MB) and leukemia patients. MiRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…(Weber et al, 2010). A number of clinical studies have shown that heightened expression of specific miRNAs is closely associated with malignant tumors, in particular the miRNAs contained in the CSF of brain tumor patients show promise as diagnostic biomarkers (Grotzer et al, 2015;R. Shi et al, 2015).…”
Section: Fluid Biomarkers In Glioma Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…(Weber et al, 2010). A number of clinical studies have shown that heightened expression of specific miRNAs is closely associated with malignant tumors, in particular the miRNAs contained in the CSF of brain tumor patients show promise as diagnostic biomarkers (Grotzer et al, 2015;R. Shi et al, 2015).…”
Section: Fluid Biomarkers In Glioma Diagnosismentioning
confidence: 99%
“…Circulating miRNAs exist in almost all human body fluids including blood, serum, urine, saliva, tears, and CSF ( Weber et al, 2010 ). A number of clinical studies have shown that heightened expression of specific miRNAs is closely associated with malignant tumors, in particular the miRNAs contained in the CSF of brain tumor patients show promise as diagnostic biomarkers ( Grotzer et al, 2015 ; R. Shi et al, 2015 ). One study in particular identified that metastatic tumor miRNA (i.e., miRNA-125a, miRNA-125b and miRNA-1290) was over-expressed in CSF samples, corresponding to expression levels in the tumor.…”
Section: Fluids and Flows In Brain Cancermentioning
confidence: 99%
“…Zajímavé je, že c-miRNA jsou vysoce stabilní a odolávají extrémním podmínkám, jako je aktivita ribonukleáz, opakované zmrazování, var, nízké a vysoké pH nebo i skladování při pokojové teplotě [13]. Deregulované hladiny miRNA v CSF jsou podle nedávných studií také asociovány s maligními nádory CNS [14][15][16][17][18][19][20]. Například hladina miR-21 u pacientů s gliomy dokázala rozlišit nádorové vzorky CSF s vyšší citlivostí a specificitou než hladiny miR-21 detekované v krevní plazmě [21].…”
Section: Cirkulující Mirnaunclassified